RELIGIOUS VALUES IN NICHOLAS SPARKS’S A WALK TO REMEMBER - Viator Lumban Raja; Indah Suryani Silitonga (Muse: Jurnal of Art, 2024)
This article discusses religious values in Nicholas Sparks’ "A Walk To Remember." The novel is considered a representation of individuals holding religious values, facing life with the belief that miraculous events shape one's existence. Conducted as a library research, this study applies mimetic theory proposed by Abrams, asserting that literature imitates real life. The analysis centres on religious values represented by the characters Landon, Jamie Sullivan, and Heghbert Sullivan. The author introduces Landon, who, through his affection for Jamie, experiences a positive transformation. Jamie, a religious woman devoted to serving orphanage children, becomes a catalyst for Landon's change into a better person. Landon holds unwavering faith in Jamie's recovery from illness. Jamie, facing numerous life challenges, proves that love and faith can lead to positive transformations, even for someone like Landon, initially perceived as a criminal and brutal. Heghbert, a priest living with his daughter, showcases the struggles of a father caring for his child. Landon's consistent devotion to Jamie demonstrates the power of love and affection. In conclusion, Nicholas Charles Sparks vividly portrays characters with religious values in faith, love, and devotion. The novel focuses on the positive aspects of life, encouraging optimism and strong faith to overcome deficiencies, suffering, and difficulties.